Modern Interpretation of the Diagnosis, Treatment and Prevention of Divergent Strabismus with a Vertical Component (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
The complexity of the structural and functional organization of the visual and oculomotor systems determines the variety of types of strabismus (heterotropia), which are the result of damage to the organ of vision, differing in etiology and location. The success of strabismus treatment, especially surgical, largely depends on the correct determination of its type. This is facilitated by a rational classification of types of strabismus, which should reflect their etiology and facilitate the choice of treatment method. Many clinical classifications of strabismus have been proposed, which to a greater or lesser extent take into account the etiological factors of this disease and its main clinical symptoms. The rapid development of diagnostic methods for lesions of various parts of the binocular visual system at the end of the 20th century contributed to the clarification of the etiology of already known types of strabismus and the identification of its new clinical varieties, which led to the need to clarify and expand the classification of this disease. Currently, ophthalmologists in Europe and America use more sophisticated classifications that more fully cover the currently known types of strabismus and more accurately reflect their etiology and clinical features. A review of these classifications shows that the traditional division of strabismus remains clinically relevant to this day. With combined strabismus, there is no violation of eye motility, the angles of primary and secondary deviation are equal, the same in all directions of gaze, or their difference does not exceed 5 pr. This is called the primary or main form of strabismus. Currently, combined strabismus also includes such types of strabismus as syndromes A, V, X, in which the angle of deviation when turning the eyes up and down differs from the angle of deviation in the main position of the eye by more than 5 pr. diopters, as well as dissociated horizontal deviation of the eyes in the absence of DHDvi. Their difference is more than 5 pr, but eye mobility is normal.